Vaccine profile of herpes zoster (HZ/su) subunit vaccine - Anthony L. Cunningham; Thomas Heineman (Taylor & Francis Group, 2017)
Introduction: Herpes zoster (HZ) causes an often severe and painful rash in older people and may be complicated by prolonged pain (postherpetic neuralgia; PHN) and by dissemination in immune-compromised patients. HZ results from reactivation of latent varicella-zoster virus (VZV) infection, often associated with age-related or other causes of decreased T cell immunity. A live attenuated vaccine boosts this immunity and provides partial protection against HZ, but this decreases with age and declines over 8 years. Areas covered: A new HZ subunit (HZ/su) vaccine combines a key surface VZV glycoprotein (E) with a T cell-boosting adjuvant system (AS01B) and is administered by two intramuscular injections two months apart. Expert commentary: HZ/su showed excellent efficacy of ~90% in immunocompetent adults ≥50 and ≥70 years of age, respectively, in the ZOE-50 and ZOE-70 phase III controlled trials. Efficacy was unaffected by advancing age and persisted for >3 years. Approximately 9.5% of subjects had severe, but transient (1-2 days) injection site pain, swelling or redness. Compliance with both vaccine doses was high (95%). The vaccine will have a major impact on HZ management. Phase I-II trials showed safety and immunogenicity in severely immunocompromised patients. Phase III trial results are expected soon.